Associations between cardiovascular risk factors, biomarkers, and left ventricular mechanical dispersion: insights from the ACE 1950 Study. Issue 2 (12th February 2022) - Aagaard, Erika N; Lyngbakken, Magnus N; Kvisvik, Brede; Berge, Trygve; Pervez, Mohammad O; Ariansen, Inger; Tveit, Arnljot; Steine, Kjetil; Røsjø, Helge; Omland, Torbjørn
Abstract: Aims: Mechanical dispersion measures left ventricular contraction heterogeneity and is associated with the risk of sudden cardiac death. However, the associations between mechanical dispersion and cardiovascular risk factors in early mid-life, and established biomarkers of sub-clinical myocardial injury and dysfunction are not known. We aimed to examine this in the general population. Methods and results: During 2012–15, we included 2527 Norwegian individuals from the general population born in 1950, with measurements of mechanical dispersion by 2D speckle tracking echocardiography and concentrations of high-sensitivity cardiac troponin T (hs-cTnT) and N-terminal pro-B-type natriuretic peptide (NT-proBNP) available. Mechanical dispersion was calculated as the standard deviation of the contraction duration of 17 strain segments. We assessed the associations between mechanical dispersion, concentrations of hs-cTnT and NT-proBNP, and cardiovascular risk factors collected at a national health screening survey two decades earlier. At echocardiography baseline, median age was 64 (interquartile range 63.5–64.5) years, 49.8% were women, 59.1% had hypertension, and 5.9% reported established coronary artery disease. Median mechanical dispersion was 38.0 (29.5–47.0) ms, median hs-cTnT concentration 6 (4–8) ng/L, and the median NT-proBNP concentration 54 (34–93) ng/L. Mechanical dispersion was associated with both hs-cTnT and NT-proBNP concentrations in multivariable models adjusted for clinical and echocardiographic variables. High body mass index, serum triglyceride concentrations, and low resting heart rate at Age 40 were independently associated with increased mechanical dispersion two decades later. Conclusion: Established risk factors at Age 40 are associated with mechanical dispersion two decades later, and mechanical dispersion is cross-sectionally associated with biomarkers of subclinical myocardial injury and dysfunction. Graphical Abstract: